Insights into Auxin Signaling in Plant–Pathogen Interactions - Wang, Shiping; Fu, Jing (Frontiers in Plant Science, 2011)
The phytohormone auxin has been noted as a regulator of plant growth and development ever since its discovery. Recent studies on plant–pathogen interactions make auxin a key character in pathogenesis and plant defense. In addition to plants, diverse pathogens possess the capacity to synthesize indole-3-acetic acid (IAA), the major form of auxin in plants. The emerging knowledge on auxin signaling components, auxin metabolic processes, and indole-derived phytoalexins in plant responses to pathogen invasion has provided putative mechanisms of IAA in plant susceptibility and resistance to non–gall- or tumor-inducing pathogens.